Manajemen Kurikulum di SMP Muhammadiyah 7 Yogyakarta - Khaerudin, Khaerudin; Setiawan, Farid; Yuliani, Aulia (MASALIQ, 2022)
The existence of educational curriculum management is a form of collaborative effort or effort to encourage the achievement of learning objectives, especially to improve the quality of teaching and learning interactions. This requires a series of evaluation, planning and implementation that cannot be separated from the unit. On the other hand, learning management is a part of a system with interrelated components. The learning components in an educational structure include students (students), teachers (educators), materials, curriculum, school infrastructure, and learning method strategies. In curriculum management and learning thus interrelated in education to achieve the desired goals. Curriculum management is an important part that influences the success of education in national education. In addition, because the curriculum is a support system to achieve institutional goals in an educational institution, the curriculum has an important role in realizing and creating quality schools. To support the success of the curriculum, the government sector or must be empowered to lead the curriculum. Curriculum management at the institution or school level must be coordinated by management (administrators) and assistant supervisors (administrators) which are developed as a whole in the context of the SBM and unit level curriculum. (KTSP) and the vision and mission of the educational institution. In this study, the method we use is direct observation at the school by interviewing the school and the supporters in making this journal are using library research or literature study which includes theories relevant to the problem in research. The library study itself is a series of activities related to collecting library data, reading, recording and processing data from a research.